The Good Luck Girls of Shipwreck Lane - Harms, Kelly (Thomas Dunne Books, 2013)
Janine Brown of Cedar Falls, Iowa, is this year's lucky winner of a brand-new, fully loaded dream home! Problem is, which Janine Brown? Janine "Janey" Brown is at first reluctant to give up the safety and sanctity she finds in her tiny kitchen. Across town, Janine "Nean" Brown knows that this house promises an escape from the latest in her revolving door of crappy jobs and drunk boyfriends. Both Janine Browns head for Christmas Cove, Maine, to claim the prize they both rightfully think is theirs.